Problematic Pornography Use in Adolescents: From Prevention to Intervention - Testa, Giulia; Mestre-Bach, Gemma; Chiclana Actis, Carlos; Potenza, Marc N. (Current Addiction Reports, 2023)
Purpose of the Review: Pornography use is common among adolescents. Adolescents may use pornography for sex education. Early exposure to pornography may have negative consequences and elevate risk of problematic pornography use (PPU). Thus, there is a need for better understanding of and effective interventions for youth viewing of pornography. This article reviews studies investigating prevention and treatment of PPU in adolescents, discussing current issues and future directions. Recent Findings: Prevention studies include pornography education based on media-literacy approaches. These programs are aimed at helping young people develop critical thinking and understanding of the nature of pornography. Some recommendations for pornography-education programs have emerged from the prevention literature such as the relevance of using age-appropriate content and participatory teaching and learning methods that involve appropriately trained staff. Treatment studies of PPU in adolescents are lacking, although the preliminary efficacy of cognitive behavioral therapy and mindfulness-based approaches has been shown in adults with PPU. Online therapeutic approaches may have benefits with adolescents. Summary: The current state of evidence indicates only a limited number of prevention studies addressing pornography education and an absence of studies evaluating PPU treatments in adolescents. There is a call for future evidence-based research to tailor PPU interventions for adolescents and to evaluate their effectiveness.
Keywords: addictive behavior; adolescents; compulsive behavior; compulsive sexual behavior; prevention; problematic pornography use; treatment; JCR; Scopus